Aves de la ribera colombiana del rio negro (frontera de colombia y venezuela) (1948)
The authors list 77 species and subspecies of birds collected on the Colombian bank of the Rio Negro, one of the larger northern tributaries of the Amazon. The Rio Negro, known as Guainía ("Huaynía") in the upper part of its course, forms the natural border of Colombia and Venezuela before entering the territory of Brazil. Of the birds listed, 74 were taken by Manuel Castro for the Coleccion ornitológica Phelps (Caracas, Venezuela), at San Felipe (opposite San Carlos, -Venezuela) and Macacuní (opposite El Carmen, Venezuela) in August-September, 1947. The authors also record the birds collected by Ernest G. Holt, Emmet R. Blake, and Charles T. Agostini in January, 1931, opposite San Carlos, Venezuela, i. e. San Felipe, Colombia. Among the nine species secured by these collectors three are not represented in Castro's 1947 collection. Sixteen birds are recorded as new to the avifauna of Colombia. The introduction of the paper mentions the naturalists who have explored the Rio Negro and the Guainía since Humboldt's celebrated voyage in 1800, and includes geographical notes, a map, and a brief description of the ecology of the region.